UNDESENSUS TESTIS (UDT) - Abdul Raziq Jamil (Nusantara Hasana Journal, 2026)
Undescended testis (UDT), also known as cryptorchidism, is a congenital disorder of the male reproductive system characterized by the failure of one or both testes to descend into the scrotum. It is one of the most common urogenital abnormalities in male infants, particularly among those born prematurely. The etiology of UDT is multifactorial, involving genetic, hormonal, environmental, and anatomical factors that interfere with the normal process of testicular descent. Diagnosis is primarily based on medical history and physical examination, while imaging studies are reserved for selected cases. Untreated UDT may lead to several complications, including impaired fertility, testicular atrophy, inguinal hernia, testicular torsion, and an increased risk of testicular cancer later in life. This review aims to examine the epidemiology, pathophysiology, diagnosis, and management of UDT based on current scientific literature. The findings indicate that orchiopexy is the primary treatment of choice and should ideally be performed before 18 months of age to optimize reproductive function and reduce the risk of long-term complications. Hormonal therapy has a limited role and is not routinely recommended. Early detection and appropriate management are essential to improve prognosis and quality of life in patients with undescended testis.